2022
DOI: 10.1039/d2nr03645b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of Ru-single-atoms on ordered mesoporous phosphine polymers for microwave-assisted conversion of biomass-derived sugars to artificial sweeteners

Abstract: Atomically dispersed metal-single-atoms have become a frontier in solid catalysis due to their characteristics electronic properties. However, for biomass conversion employing metal-single-atoms as catalysts is rather challenging since it suffers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…The major peak as observed at 2.35 Å is clearly indicating Ru–P coordination as justified from a prior report that discloses atomic dispersion of Ru-single atom under the influence of phosphorus-based ligands . Additionally, reported phosphine ligands, i.e., ordered phosphine polymers, BINAP-POP, and other phosphine support, control the atomic dispersion of Ru due to its unique ligand effect, which is henceforth reflected in this research. Thus, based on the previous reports as well as from our experiments, it is indicated that better atomically dispersed single-atom ruthenium is formed in PPh 3 PO/PPh 3 P modified on the mesoporous silica host (Ru@SiP).…”
Section: Synthesis Of Triphenylphosphine-modified Mesoporous Silica (...supporting
confidence: 81%
“…The major peak as observed at 2.35 Å is clearly indicating Ru–P coordination as justified from a prior report that discloses atomic dispersion of Ru-single atom under the influence of phosphorus-based ligands . Additionally, reported phosphine ligands, i.e., ordered phosphine polymers, BINAP-POP, and other phosphine support, control the atomic dispersion of Ru due to its unique ligand effect, which is henceforth reflected in this research. Thus, based on the previous reports as well as from our experiments, it is indicated that better atomically dispersed single-atom ruthenium is formed in PPh 3 PO/PPh 3 P modified on the mesoporous silica host (Ru@SiP).…”
Section: Synthesis Of Triphenylphosphine-modified Mesoporous Silica (...supporting
confidence: 81%
“…Ni SA as Lewis acid and the neighbouring pyridinic site as Lewis base promotes hydrogenation and is imperative as a stable catalyst. Modak et al [19] reported an interesting Ru single atom catalyst that shows catalytic transfer hydrogenation of xylose and glucose to xylitol and sorbitol respectively, in a microwave reactor involving a green and mild reaction protocol, avoiding the use of pressurized reactor. Importantly, Ru-SA on triphenylphosphinecontaining ordered mesoporous polymer has pronounced transfer hydrogenation activity than commercial Ru/C and Ru SA grafted on other polymers viz.…”
Section: Hydrogenationmentioning
confidence: 99%
“…For example, Ru@PPhMesoSi is an excellent catalyst for the microwave synthesis of xylitol and sorbitol as important sugar substitutes from hydrogenation of xylose and glucose respectively. [19] On the contrary, Ru-nanoparticles [28] and other bimetallic nanoparticles [29] are inactive for xylose hydrogenation in the microwave, but is an active catalyst under the harsh condition in a Parr reactor (high T & P). Under such context, SACs have shown progressive attention in the upgradation of complex feedstocks like cellulose, hemicellulose, and lignin which are the rich sources of chemicals and fuels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations